Rumble in the jungle - Giles Andreae (London; Orchard Books, 2017)
Come into the jungle for a noisy, rhyming animal adventure in this bright bold board book! There's a rumble in the jungle, There's a whisper in the trees, The animals are waking up, And rustling the leaves ...Little ones will love looking at all the colourful pictures and joining in, as they discover all sorts of jungle animals - including lions, elephants, chimpanzees, zebras, hippos and more! With rhyming, read-aloud text from Giles Andreae, the author of international bestseller Giraffes Can't Dance, this classic first storybook has been delighting families for over 20 years.
Keywords: Board books